Application of THz-TDS Technology in on-line detection of vacuum degree of arc extinguishing chamber. Issue 1 (February 2021) - Yang, Yongxu; Dong, Jinxiang; Yue, Feng; Zhang, Kun; Li, Wei
Abstract: Terahertz time-domain spectroscopy (THz-TDS) is a non-destructive detection technology for carrying information inside a sample through a wide-band terahertz pulse carrying medium information. This paper briefly describes the imaging principle, characteristics, development and application direction of THz-TDS technology. The theoretical basis of THz-TDS technology applied in vacuum degree on-line monitoring is analyzed and verified by experiments. The experimental results show that with the change of vacuum degree, the signal amplitude attenuation and time delay of THz spectrum will change regularly. It shows that the spectrum and absorption spectrum obtained by THz-TDS imaging technology can sensitively distinguish the change of pressure in vacuum environment, that is, the change of vacuum degree. At the same time, the related air environmental pollution information also has strong absorption characteristics in the terahertz band, which makes the use of terahertz spectroscopy technology to detect pollutants in the atmosphere have a good development prospect.